Dietary exposure and health risk characterization of aflatoxin B1, ochratoxin A, fumonisin B1, and zearalenone in food from different provinces in Northern Vietnam. (June 2020) - Do, Tuan Huu; Tran, Son Cao; Le, Chi Dinh; Nguyen, Ha-Binh Thi; Le, Phuong-Thao Thi; Le, Hong-Hao Thi; Le, Tuyen Danh; Thai-Nguyen, Hung-Thu
Abstract: A dietary exposure and health risk assessment of mycotoxins including aflatoxin B1, fumonisin B1, ochratoxin A, and zearalenone was conducted in 3 provinces in Northern Vietnam namely Hanoi, Thanh Hoa, and Ha Giang. Results of the analysis of samples of maize, rice, peanut, and sesame revealed the presence of these mycotoxins in all samples and sampling locations. Aflatoxin B1 was the most frequently detected (19.1%) and widely distributed among different types of samples, whereas the percentage occurrence of fumonisin B1, ochratoxin A, and zearalenone were 11.2, 5.9 and 6.3, respectively. The later three mycotoxins were detected mostly in maize. The exposure to aflatoxin B1 at detected levels could lead to 0.23, 0.65 and 21.0 cases of liver cancer per 100, 000 adult people per year in Hanoi, Thanh Hoa and Ha Giang, respectively. The risk assessment also showed the unsafe exposure to ochratoxin A and fumonisin B1 in the highland region where the people consume a large amount of foods derived from maize. In Ha Giang, the mean exposures to fumonisin B1 were lower than its PMTDI (Provisional Maximum Tolerable Daily Intake), however, the 95th percentile values were 1.1–1.9 times of the PMTDI. The mean exposures to ochratoxin A in Ha Giang were about 2.4–3.6 times higher than its PMTWI (Provisional Maximum Tolerable Weekly Intake). There was no risk of fumonisin B1 and ochratoxin A in Hanoi and Thanh Hoa. The dietary exposure to zearalenone was within its PMTDI in all locations. The results pointed out the need for further improvement of the control of these mycotoxins in Vietnam, especially in some highland provinces. Highlights: Higher mycotoxins content in food in Ha Giang compared to other localities. High exposure doses of mycotoxins in highland due to long storage time of maize. Different liver cancer risk caused by aflatoxin B1 exposure in three provinces. Unsafe exposure to ochratoxin A and fumonisin B1 in the highland region. No risk caused by zearalenone exposure in the studied provinces.